Thermodynamic study and performance simulation of a renewable-based Kalina cycle in distributed generation. (2nd January 2017) - Sameti, Mohammad; Ghasemipour, Seyedeh Sahar
Abstract: A major advance in affordability of solar electricity may occur with Kalina solar system which offers a path to provide an efficient heat-to-electricity. In this study, a comprehensive thermodynamic model is introduced to simulate a Kalina cycle which exploits solar thermal energy as the source to be used in distributed generation. Ammonia–water mixture was considered as the working fluid where its thermos-physical behavior was modeled using detailed correlation in the cycle. A case study is performed for different cities of Iran to evaluate the potential of the proposed system for supplying electricity for residential sector. The results showed that in some sites, the production exceeds the demands for almost 25%.